GBT440 reverses sickling of sickled red blood cells under hypoxic conditions in vitro - Kobina Dufu (Hematology Reports, 2018)
Sickle cell disease is characterized by hemolytic anemia, vasoocclusion and early mortality. Polymerization of hemoglobin S followed by red blood cell sickling and subsequent vascular injury are key events in the pathogenesis of sickle cell disease. Sickled red blood cells are major contributors to the abnormal blood rheology, poor microvascular blood flow and endothelial injury in sickle cell disease. Therefore, an agent that can prevent and or reverse sickling of red blood cells, may provide therapeutic benefit for the treatment of sickle cell disease. We report here that GBT440, an anti-polymerization agent being developed for the chronic treatment of sickle cell disease, increases hemoglobin oxygen affinity and reverses in vitro sickling of previously sickled red blood cells under hypoxic conditions. Our results suggest that besides preventing sickling of red blood cells, GBT440 may mitigate vasoocclusion and microvascular dysfunction by reversing sickling of circulating sickled red blood cells in vivo.